The Self After Official Disdain: The Analysis of Ontologically Weak Identity (Diametros, 2025)
The aim of the article is twofold: to analyze the different possible reactions of a subject to institutional humiliation, and to ground these reactions in different habits of self-ontologization, differentiating between weak and strong models of identification. In order to illustrate the analyzed theoretical distinctions, I use two cases in the article: two narratives of individuals who experienced the disdain of officials because of their non-normative bodies. Both people were confronted with the norms and concepts prevailing in society that humiliate them in the most symbolic expression of normativity. However, this encounter led to completely different attitudes towards social order and modes of self-identification. The article consists of three chapters. In the first chapter, I will discuss two basic conceptions of identification and raise a question about their forms in practice. In the second chapter, I relate one of these ways to the concept of process ontology (and particularly to the concept of the incorporeal) and discuss the different possible types of self-ontologization in situations of official disdain. The third chapter is devoted to the relationship between power and the subject: the ambiguous character of power is revealed and two different reactions (surrendering to power, and assuming resistant power) are related to the modes of self-ontologizing. I also rethink the concept of vulnerability in two different ways, revealed by the cases analyzed: vulnerability is discussed in relation to either the concept of resistance or the concept of resilience, which lead back to  different conceptions of identity.